INTRODUCTION OF THE WILD TURKEY INTO THE CARLOS AVERY WILDLIFE MANAGEMENT AREA - Gregory L. McMahon; Roger N. Johnson (Wildlife Society Bulletin)
Abstract During the winter of 1978‐79, 19 wild turkeys (Meleagris gallopavo) were rocket‐netted in the Whitewater Wildlife Management Area in southeastern Minnesota, equipped with radio‐transmitters, and released into the Carlos Avery Wildlife Management Area in east‐central Minnesota. The release area is approximately 160 km north of the northern limit of the historical range of the wild turkey in Minnesota. Fifty three percent of the wild turkeys released were lost to predation or starvation. Newly released wild turkeys traveled an average of 2.4 km from their release sites before settling into a wintering area and it was during this movement that predation generally occurred. Snow depth at the time of movement from the release site appeared important in determining whether or not predation occurred. Home ranges averaged 750.2 ha for the winter months and increased to an average of 1,520.8 ha for the spring months. During spring, both males and females made numerous long trips into surrounding residential and agricultural areas but always returned to the Wildlife Management Area. Spring dispersal distances averaged 2.77 km for females and 2.05 km for males. Summer movements were minimal and home ranges averaged only 174.8 ha. Reproductive success was limited. Although 5 out of 6 hens attempted to nest, only 1 hen was successful in hatching eggs. Egg predation was the major cause of nesting failure.